Vertebra Plana: A Narrative Clinical and Imaging Overview among Possible Differential Diagnoses - Andrea Angelini; Nicolò Mosele; Andrea Gnassi; Riccardo Baracco; Maria Grazia Rodà; Mariachiara Cerchiaro; Pietro Ruggieri (Diagnostics, 2023)
Vertebra plana is a rare radiologic condition characterized by a uniform loss of height of a vertebral body that represents a diagnostic challenge for surgeons. The purpose of this study was to review all possible differential diagnoses that may present with a vertebra plana (VP) described in the current literature. For that purpose, we performed a narrative literature review in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, analyzing 602 articles. Patient demographics, clinical presentation, imaging characteristics and diagnoses were investigated. VP is not a pathognomonic feature of Langerhans cell histiocytosis, but other oncologic and non-oncologic conditions should be considered. The list of differential diagnoses, based on our literature review, can be recalled with the mnemonic HEIGHT OF HOMO: H—Histiocytosis; E—Ewing’s sarcoma; I—Infection; G—Giant cell tumor; H—Hematologic neoplasms; T—Tuberculosis; O—Osteogenesis imperfecta; F—Fracture; H—Hemangioma; O—Osteoblastoma; M—Metastasis; O—Osteomyelitis, chronic.